Pengaruh Latihan Kecepatan terhadap Kemampuan Menggiring Bola dalam Permainan Sepak Bola di Klub Tunas Harapan Bengkulu Selatan - Mardansya, Doni; Syaputra, Roni; Martiani, Martiani (Educative Sportive, 2025)
This study aims to determine the effect of speed training on dribbling skills in soccer players at Club Tunas Harapan Bengkulu Selatan. This study used an experimental method with a pre-test and post-test design in one group (one-group pretest-posttest design). The study sample consisted of 18 players who underwent a speed training program for six weeks. Dribbling skills were measured before and after training using a zig-zag dribbling test. The results showed that there was a significant increase in dribbling skills after being given speed training. The average dribbling time before training was 20.15 seconds, while after training it decreased to 18.58 seconds. Statistical tests using paired sample t-test showed a significance value of 0.000 (p <0.05), which indicated a significant effect of speed training on improving dribbling skills. The conclusion of this study is that speed training contributes positively to improving the dribbling skills of Club Tunas Harapan Bengkulu Selatan soccer players.